Improving the Managerial Capacity of Al Washliyah School Principals through a Strategic Workshop at the School Leaders Forum - Larasati Nur Kharomah; Rismayanti Rismayanti; Arya Prandana (Indonesia Berdaya, 2026)
This community service program aimed to enhance the managerial capacity of school principals under the auspices of Al Washliyah through strategic workshops conducted within the School Leaders Forum. The program employed a Service Learning approach that integrated academic knowledge with practical engagement to address real managerial challenges faced by school leaders in the era of educational reform and Society 5.0. The preparation stage involved a needs assessment, literature review, and SWOT analysis to ensure that the intervention was contextually relevant and responsive to institutional conditions. Based on this analysis, a competency-based workshop curriculum was developed, focusing on conceptual, technical, and interpersonal managerial skills. The program was implemented through a series of strategic workshop sessions covering educational strategic planning, alignment with the National Education Standards, digital leadership, teacher performance management, and stakeholder collaboration. The results indicate that the program contributed to improved strategic thinking, increased digital awareness, and strengthened supervisory and motivational competencies among participating principals. Furthermore, the School Leaders Forum functioned as an effective professional learning community that facilitated peer collaboration and reflective leadership practices. Overall, the program demonstrates that structured capacity-building initiatives conducted through professional forums can support the transformation of school principals into instructional and transformational leaders, thereby fostering sustainable improvements in school quality and organizational competitiveness.